Community liquid waste management system in Gili air tourism area and its management strategy based on a SWOT analysis - Edy Swandayani, Rosaina; Pahriana Sulastri, Meilinda (International Journal of Biological Research, 2021)
Lombok island is one of the international tourism destinations because of its topography and natural beauty which has its own charm for both domestic and foreign tourists. One of the famous marine tourism destinations on the island of Lombok is Gili Air. Most of the waste problems in Gili Air are domestic liquid waste, both from community waste and tourism business waste. This study is a descriptive exploratory study by exploring and describing the liquid waste management system by the community, hotel managers and restaurants in the tourism area of Gili Air. The observations were made in residential areas, hotels and restaurants on Gili Air. The determination of sampling areas and resource persons is determined by purposive sampling. Data were collected by conducting a survey at the research location through direct observation and interviews with informants. SWOT analysis were used to determine a liquid waste management strategy in Gili Air. Based on the study conducted in Gili Air, which includes residential areas, hotels and restaurants, the liquid waste management system is carried out individually using a septic-tank, land use management for wastewater with a septic tank placed at the side / back of the house and a waste management strategy can be implemented by establishing a communal and environmentally friendly waste management facility in the form of a Waste Final Disposal Plant (IPAL) for liquid waste.Â Â